If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying gr + 5n = yf Solving gr + 5n = fy Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-5n' to each side of the equation. gr + 5n + -5n = fy + -5n Combine like terms: 5n + -5n = 0 gr + 0 = fy + -5n gr = fy + -5n Divide each side by 'r'. g = fr-1y + -5nr-1 Simplifying g = fr-1y + -5nr-1
| 2x*lnx+x=2 | | 9(a+b)9a+x= | | 2x-2.3=x-107 | | 8x+3.5=-7x+-2.1 | | 5(4x+7)=15 | | 0=2(n/5)-6(4n-2) | | a^4+2a^3-a^2-20= | | x-(0.06*x)=50000 | | 8/3x3 | | m^6-729= | | -3(4x+9)=-171 | | (8/3)(3) | | 1-2a^3+a^6= | | y=-3x+45 | | 6(8-7x)=6 | | pq+5=13forp | | 99.2/6.2 | | y=3x-45 | | t=3(3a+4)(3a+4) | | -5(-6x+9)=255 | | (6p-24)+9=23 | | 20-x=6x+6 | | a^2x^3-a^2y^3+2ax^3-2ay^3= | | 3(-2x-6)=-78 | | 4x+3.4=5x-1.1 | | -2x-2x=16 | | 18y+2=29 | | x-9=19+2 | | 11x+7.5=90 | | 2.3y-5.18=51.9 | | x-9=19+z | | -7+6x-7x=-11 |